2011
DOI: 10.3390/molecules16064539
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Cytotoxic Investigations of Curcuma mangga Rhizomes

Abstract: Investigations on the cytotoxic effects of the crude methanol and fractionated extracts (hexane, ethyl acetate) C. mangga against six human cancer cell lines, namely the hormone-dependent breast cell line (MCF-7), nasopharyngeal epidermoid cell line (KB), lung cell line (A549), cervical cell line (Ca Ski), colon cell lines (HCT 116 and HT-29), and one non-cancer human fibroblast cell line (MRC-5) were conducted using an in-vitro neutral red cytotoxicity assay. The crude methanol and fractionated extracts (hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 15 publications
4
50
0
2
Order By: Relevance
“…It can be found in most tropical countries such as Indonesia, Malaysia, and Thailand [3]. C. mangga is locally known as "temu mangga" in Indonesia and is highly valued in folk medicine for its healing properties to treat stomach disorders, fever, and cancer-related diseases [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found in most tropical countries such as Indonesia, Malaysia, and Thailand [3]. C. mangga is locally known as "temu mangga" in Indonesia and is highly valued in folk medicine for its healing properties to treat stomach disorders, fever, and cancer-related diseases [4].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies on C. mangga have resulted in the isolation of various compounds, including β-sitosterol, curcumin, (E)-labda-8(17),12-dien-15,16-dial, zerumin A (E)-15,16-bisnorlabda-8(17),11-dien-13-one, demethoxycurcumin and bisdemethoxycurcumin [4,5]. C. mangga has been reported to have analgesic and anti-inflammatory activities [6].…”
Section: Introductionmentioning
confidence: 99%
“…mangga was found to contain various organic compounds including polyphenols, flavonoids, triterpenes, and sterols [6,7]. The plant was reported to have curcuminoid as its major components; these include curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC).…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior to the report by Abdul Malek et al [43], Alpinia mutica was previously reported to have inhibitory activity towards lipid oxidation [50] and anti-bacterial effects against Bacillus subtilis and methicillin-resistant Staphylococcus aureus (MRSA) [50] in addition to anti-platelet aggregation activities [51].…”
Section: Ht29 and Ccd-18comentioning
confidence: 99%